Trichoderma harzianum-based novel formulations: potential applications for management of Next-Gen agricultural challenges - Fraceto, Leonardo F [UNESP]; Maruyama, Cintia R [UNESP]; Guilger, Mariana; Mishra, Sandhya; Keswani, Chetan; Singh, Harikesh Bahadur; de Lima, Renata (Wiley, 2018)
Fungi of the Trichoderma spp. genus, notably Trichoderma harzianum, are commonly used for biological management of deleterious seed- and soil-borne pathogens. The global biopesticides market is booming with a major share of various commercial formulations of T. harzianum. However, there are some major drawbacks associated with these commercial formulations including short shelf life, low on-field stability and irregular performance in different agro-climatic regions. For effectively resolving these issues, new strategies are urgently required for efficient management of pathogens. The present review provides an overview of the use of Trichoderma spp., with special emphasis on T. harzianum, and discusses future trends for biological control. Technologies are described for the microencapsulation of fungi and for the biogenic synthesis of nanoparticles, with the aim of improving the biological control of pathogens and contributing to sustainable agricultural practices. © 2018 Society of Chemical Industry.
Keywords: biological control; eco-friendly; microencapsulation; nanotechnology; phytopathogens; sustainable agriculture; Trichoderma harzianum